Green Human Resource Management as a Predictor of Green Supply Chain Management Practices: Evidence from Thai Hotels - Ratchada Fongtanakit; Boonsri Suteerachai (International Journal of Supply Chain Management, 2019)
Organizations are embracing the â€œgo greenâ€ concept. It is being implemented in the internal and external organizational boundaries with the primary aim to establish a superior environmental and financial performance. Bearing in mind the importance of the topic current study examined how the GRHM do contributes towards the GSCM. An empirical study was conducted to examine the aforementioned relationship and for this purpose data were collected from 200 managers of hotels in Phuket Thailand. Smart-PLS have been employed for the data analysis. Data analysis revealed a significant association between independent variables (green compensation, green performance appraisal, green training and green hiring) and dependent variable (green supply chain management practices). All the relationships between the variables were in positive direction. Further the results also revealed a weak association between green performance management and compensation and green supply chain management practices (GSCMP). Which may be due to sense of responsibility of the employees towards the environment protection.